The Implementation of Restorative Justice in Tipiring Cases as an Effort to Reduce Suspects in Detention - Dani Kurniawan; Dedi Wardana Nasoetion; M. Syahrul Borman (Rechtsvinding, 2026)
This study examines the application of restorative justice in handling minor criminal offenses as an effort to reduce the number of detainees in detention centers. The current handling of minor offenses in Indonesia is often considered disproportionate, as imprisonment is frequently imposed despite the relatively small impact of such crimes. This situation contributes to overcrowding in correctional institutions and increases the burden on the criminal justice system. Restorative justice offers an alternative approach that emphasizes dialogue, mediation, and reconciliation between the offender and the victim in order to restore the social relationship that has been disrupted by the crime. This research employs a normative juridical method by analyzing relevant laws, regulations, and legal literature concerning the implementation of restorative justice in Indonesia. The findings indicate that restorative justice can provide a more effective, humane, and efficient solution in resolving minor criminal cases. Through this approach, victims can obtain compensation and a sense of justice, while offenders are given the opportunity to take responsibility and reintegrate into society without the negative stigma of imprisonment. Therefore, restorative justice can serve as an important instrument in reducing the number of detainees and improving the effectiveness of the criminal justice system in Indonesia